Hyper consumerist behavior of K-pop commodity by the Carat community - Cabello, Gyle Viannelou R.
Hyper consumerism is defined as the extreme maximalist consumption of goods and commodities for non-functional purposes (Cyr, 2019), and K-pop fans are seen to display tendencies described in this behavior. This study aims to determine the income allocation of K-pop fans, specifically the Carats (Seventeen's Fandom), on K-pop merchandise. It also aims to measure the hyper consumerist tendencies of the Carat fandom using the Hyper Consumerist Behavior Scale by Dmitrova et al. The study used ordinal logistic regression on the answers of 215 online respondents and categorized them based on income and merchandise expenditure. The results showed that more than 45% of respondents allocate more than half of their income to K-pop merchandise. The regression also showed that individual monthly income/allowance, merchandise expenditure, perceived repair benefits, possession of large amounts of goods, and experiential consumption are significantly related to shopping control. Moreover, it showed that as income increases shopping control decreases, implying that respondents at higher incomes can control their merchandise purchasing behavior better.